Intrinsic Relationships between Learning Conceptions, Preferences for Teaching and Approaches to Studying among Occupational Therapy Students in the United States. Issue 2 (3rd April 2023) - Bonsaksen, Tore; Breen-Franklin, Adele
Abstract: The aim of this study was to examine the associations between occupational therapy students' learning conceptions, preferences for teaching, and approaches to studying. The deep learning concept was associated with deep and strategic approaches to learning. The student preference for the teaching-style "transmitting information" was associated with a surface approach to learning. Understanding the interrelationships between students' learning concepts, teaching preferences, and study approaches may provide incentive for faculty members to think about novel approaches to teaching. While occupational therapy faculty members should encourage a deep learning concept and stimulate students' linking of ideas, they may need to modify their teaching style to accommodate surface-oriented students' needs.